Leadership, legitimacy and peacebuilding in Nigeria (2015)
While there exist several studies devoted to evaluating the leadership question in Nigeria, there is still a lot of ground to cover on the issue of leadership, legitimacy and peace building. This paper argues that the prevalence of internal conflicts, the attendant insecurity and political instability have been obstacles to peace and development in Nigeria. Central to the discourse is that the situation that exists in many parts of the country today where crimes, kidnapping, violent conflicts and other social vices reign supreme, is a challenge to the quality, creativity, and competence of Nigeria’s leadership at all levels. Weak legitimacy has hindered the selection of contested representation within the context of conflict resolution. Thus, the unresolved legitimate representation for peace processes has continued to escalate violent conflicts. Legitimacy is widely recognised as central to peace building. Drawing experience from local governance arrangement from across developed democracies, legitimate community representatives have not only provided basic law, security and effective conflict resolution, but have also helped to solidify inter-communal peace accords at the grassroots level. In spite of this leadership crisis, performance legitimacy can serve as an effective instrument for national peace processes in Nigeria. Hence, the prospect for managing violent conflicts in the interest of peace building and sustainable development is inherent in the application of legitimacy performance